Predictors of International Students’ Willingness to Communicate in a Foreign Language: The Mediating Role of Study Abroad Experience - Bhatti, Muhammad Awais; Juhari, Ariff Syah (Journal of International Students, 2023)
This study aims to examine the factors influencing communication among Arab students studying in Malaysia. It adopts a positivist approach and a quantitative methodology, using a questionnaire to collect data from students in Malaysian universities in the Klang Valley, including Kuala Lumpur, Selangor, and Putrajaya.Convenience sampling was employed to distribute 450 questionnaires to students, resulting in 300 valid responses. SPSS and PLS-SEM were utilized for the data analysis. The study revealed that perceived discrimination at a university negatively impacts study-abroad experience, while homesickness has no significant influence. Teacher support, on the other hand, significantly influenced study-abroad experience. The research also explored the mediating role of study-abroad experience, finding significant mediation in all relationships except for the link between homesickness and willingness to communicate.